Design and Life Cycle Assessment of small-scale medical waste incinerator equipped with Porous Radiant Burner for remote areas. Issue 5 (20th October 2022) - Mahalingam, Arun Kumar; Shaik, Sofia Rani; Kaushik, Lav Kumar; Palanisamy, Muthukumar; Kalita, Pratul Chandra
ABSTRACT: In this paper, the design of a Small-scale Medical Waste Incinerator (SMWI) equipped with an LPG-operated Porous Radiant Burner (PRBLPG ) is presented as a solution for disposing of medical waste generated in remote areas. Based on simple mass and heat balance analysis, SMWI having primary and secondary chambers with a volume of 1 and 0.754 m 3 is designed. The proposed SMWI is evaluated for its environmental impact by performing a Life Cycle Assessment (LCA) and compared with an SMWI equipped with an Electric Heater (SMWI–EH). The total primary energy required for the construction of SMWI is 48285.56 MJ. It is found that the damage caused by the operation of PRBLPG in SMWI is lesser when compared to that of an Electric Heater (EH). In SMWI–PRB, LPG consumption contributed to about 17488.27 kg CO2−eq in the global warming category, whereas in the case of SMWI–EH, electricity consumption contributed to about 243766.11 kg CO2−eq . The operation of SMWI–PRB showed a reduction of about 54% in the resource utilisation category in comparison with SMWI–EH. The results obtained from the LCA study indicated that PRBLPG is a better option as an auxiliary heating device in SMWI than EH due to its environmental superiority. GRAPHICAL ABSTRACT: UF0001